Pulmonary Recruitment Strategy in Preterm Neonates < 29 Weeks of Gestational Age to Reduce the Need for Intubation in the Delivery Room - Petrillo, Flavia; Valenzano, Luigia; Franco, Caterina; Calò, Giovanna; Dentico, Domenico; Manzoni, Paolo; D'Amato, Gabriele; Del Vecchio, Antonio (American Journal of Perinatology, 2019)
Background The application of noninvasive ventilation (NIV) modalities from birth in the delivery room (DR) during fetal–neonatal transition reduces the need for invasive mechanical ventilation, mortality, and bronchopulmonary dysplasia (BPD). The use of a RAM nasal cannula (RAM NC) in the DR for resuscitation results in less need for intubation, chest compressions, and epinephrine administration when compared with using a face mask for PPV in the DR.Objective To evaluate the need for endotracheal intubation in the DR among extremely low gestational age neonates treated at birth with sustained inflation (SI) followed by a nasal continuous positive airway pressure (NCPAP) (range: 6–8 cm of H2O) delivered through the RAM NC.Study Design A retrospective study was conducted to compare the use of NIV techniques in the DR and the need for intubation in the DR in premature infants 23 to 28 weeks' gestational age from December 2016 to July 2018 (group A). These data were compared with those of premature inborn infants with similar GA born between April 2015 and November 2016 (group B). In the DR, immediately after birth, neonates in group A received SI through RAM NC followed by CPAP ranging from 6 to 8 cm H2O, whereas the neonates in group B were treated in the DR with SI administered through a face mask followed by the application of CPAP of 5 cm H2O delivered through a nasopharyngeal tube.Results A total of 65 preterm infants 23 to 28 weeks of gestational age, 31 in group A and 34 in group B, were included in the study. The percentage of neonates intubated in the DR was significantly lower in group A (p < 0.008). In both groups, no neonates died in the DR, and no one required epinephrine and/or chest compressions. For those neonates who did not require intubation in the DR, there was no significant difference in the average FiO2 on arrival in the neonatal intensive care unit, rate of intubation within 24 hours, and use of surfactant. The incidence of BPD was similar in the two groups. Only one infant in group A developed moderate BPD, and no one needed oxygen and/or ventilatory assistance at discharge. Mortality was similar in the two groups, with a slight prevalence in group B (27.7 vs. 19.2%).Conclusion SI with RAM NC followed by NCPAP ranging from 6 to 8 cm H2O, administered with RAM NC resulted in a significant reduction of intubation in the DR.
Keywords: neonatal noninvasive ventilation; RAM nasal cannula; pulmonary recruitment; incremental PEEP in DR